Identification of a potent and highly efficacious, yet slowly desensitizing CB1 cannabinoid receptor agonist - Luk, Terry (2004)
1. The relationship of agonist efficacy to the rate of G protein-coupled receptor signaling desensitization is controversial. 2. Expressing inwardly rectifying potassium channels (GIRKs) in Xenopus oocytes, we have devised a signaling assay that clearly identifies CB1 cannabinoid receptor agonists with low intrinsic efficacy. 3. In this assay, the synthetic CB1 agonists, AM411, AM782, AM1902, AM2233 and WIN55,212-2 and the endogenous cannabinoid, 2-arachidonoyl ester, were full agonists. 4. The synthetic CB1 agonist AM356 (methanandamide), the endogenous cannabinoids, anandamide and 2-arachidonoyl ether, and the phytocannabinoid, Δ(9)THC, were partial agonists. 5. The rate of desensitization of CB1 was independent of agonist efficacy. WIN55,212-2, AM782, AM1902, AM2233, and 2-arachidonoyl glycerol ester all desensitized quickly, with desensitization rates varying from 14% min(−1) to 10% min(−1). AM356, AM411, anandamide, and Δ(9)THC all desensitized considerably slower, at a rate of 5% min(−1). 6. Despite high potency and efficacy, AM411 desensitized as slowly as anandamide and Δ(9)THC. 7. CB1 agonist efficacy and rate of desensitization are not necessarily related.